Invasive cane toad triggers chronic physiological stress and decreased reproductive success in an island endemic. (30th April 2015) - Narayan, Edward J.; Jessop, Tim S.; Hero, Jean‐Marc
Summary: Understanding the mechanisms that afford invasive species their ecological success as important agents of global change is key to addressing their biodiversity impacts. Species invasions that occur on small islands are especially detrimental and suggest that invaders intensify their ecological impacts by exploiting novel ecological functions. However, it remains unknown whether such strong impacts are also a consequence of an invader's indirect effect (e.g. causing physiological stress or reproductive failure) on island species. Therefore, it is valuable to quantify the physiological mechanisms through which invasive species can exert indirect effects on the performance, and ultimately the fitness of island endemics. In this study, we investigated whether the invasive cane toad ( Rhinella marina ) caused indirect competitive impacts on the endemic Fijian ground frog ( Platymantis vitiana ) on the small (60 ha) Viwa Island, Fiji. We used large (4 × 10 000 m 2 ), natural and replicated enclosures to monitor ground frog stress hormone levels, reproductive hormone cycle, body condition, breeding and survival in the presence/absence of the cane toad. We conducted monthly sampling to analyse annual patterns in testosterone for males, estradiol and progesterone for females, corticosterone for both sexes and body condition of ground frogs in replicated enclosures or natural habitats with high/low cane toad densities. We also measured survival and reproductive success of ground frogs in enclosures. Results showed that in both enclosures and natural habitats with high cane toad densities, ground frogs had a significant reduction in body condition, increased urinary corticosterone metabolites and suppressed sex steroid metabolites. Most importantly, annual field surveys showed significant reduction in ground frog reproductive success (fewer eggs were laid in enclosures with toads present); however, survival was not severely reduced. Our study clearly demonstrated that on small islands, invasive species may exploit broader ecological roles with strong indirect effects that amplify their impacts beyond those seen on continents. Overall, the effects of cane toad competition had the capacity to strongly reduce ground frog reproductive success. We strongly advocate management actions that either minimize invasion or limit the strength of invasive–native species interactions (e.g. through habitat conservation) to prevent further extinctions on islands. Abstract : Lay Summary